Public procurement fraud: a systematic review and bibliometric analysis of global evidence - Astuti, Wuku; Siregar, Baldric; Badrudin, Rudy; Jamaliah Said (Proceeding International Conference on Accounting and Finance, 2026)
Public procurement fraud remains a pervasive issue undermining governance and economic efficiency worldwide. This study conducts a systematic literature review to identify the determinants of public procurement fraud and assess its impacts. Given the critical role of public procurement in government spending, understanding the factors that drive fraud and its consequences is essential to improving procurement systems and governance. Using the PRISMA methodology, this study systematically analyzes 86 academic articles published between 2010 and 2024 from the Scopus database. The findings show that procurement fraud is primarily drive by inadequeate regulatory oversight, excessive discretion in decision-making, and limited use of monitoring and transparency. Its impacts are far-reaching, including significant financial losses, reduced quality of goods and services, and diminished public trust in government institutions. The lack of accountability and transparency further exacerbates these challenges. This review offers a comprehensive synthesis of contemporary research, providing valuable insights for policymakers, procurement practitioners, and scholars. It clarifies the complex nature of procurement fraud, strengthens understanding of the issue and lays a foundation for future strategies to curb fraud and improve procurement practices.